The Asymmetric Effects of Fluctuations in Oil Prices on the Performance of the Libyan Economy: A VAR Approach - Haytem Ahmed Troug; Matt Murray (International Journal of Economics and Financial Issues, 2020)
This paper examines the presence of asymmetry in the response of the Libyan economy to fluctuations in oil prices, subsequent to discovery of oil in the country. Three Vector Autoregressive (VAR) models are illustrated and estimated along with a multivariate rolling VAR approach. All sectors are found to react asymmetrically to shocks in oil prices over the 1962-2012 period. The magnitude of the adverse effect of the negative oil shocks on the manufacturing and agriculture sector appears to outweigh the positive effect of the positive oil shocks. The services sector, on the other hand, is able to overcome the shocks of the oil prices, due to absence of external competition. In addition, the results of the Multivariate rolling VAR highlight the existence of structural changes in the relationship between sectors of the Libyan economy and oil prices. The essay recommends implementing fiscal policy reform to de-link the real sector from fluctuations in oil prices. It also advises promoting the development of the financial sector in order for it to contribute in the diversification of the economy.